Papillary Thyroid Carcinoma Arising in Thyroglossal Duct Cyst: A Case Report - Fadillah (RSUP Dr Moh Hoesin Palembang, 2022)
Thyroglossal duct cysts (TGDC) are usually located in the midline of the neck. A remnant of the thyroglossal duct, usually a cyst, is the most common congenital abnormality of thyroid gland development. This study aimed to describe a patient with TGDC and the microscopic appearance of the supporting examination. A woman, 22 years old, was admitted to the hospital with complaints of a lump in the submandibular area. Excision surgery was performed, with the result microscopic showing the cyst was composed of cuboidal epithelial cells and thyroid follicles present in the cyst wall, and some histological findings, such as; formation of papillary structures, nuclear morphologic variations such as ground glass nuclei, pseudoinclusions, intranuclear grooves. Based on the clinical symptoms and histopathology, the mass in the left submandibular is consistent with papillary carcinoma arising in thyroglossal duct cysts.